2016
DOI: 10.22159/ijpps.2016v8i12.14949
|View full text |Cite
|
Sign up to set email alerts
|

Potent Biological Agent Benzimidazole–a Review

Abstract: <p>Benzimidazole nucleus is one of the most important heterocycles exhibiting remarkable pharmacological activities. Numerous method for the synthesis of benzimidazole and also their diverse reactions offer enormous scope in the field of medicinal chemistry. Various reported biological activities (analgesic, anti-inflammatory, anthelmintic, anticancer, anthelmintic, antioxidant, antitubercular, and antiviral activity) of bezimidazole are collected and summarized here. Large numbers of drugs are available… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 29 publications
0
18
0
1
Order By: Relevance
“…To clarify this point, mass spectrometry analysis of a particle suspension supernatant allowed us to identify the presence of gentamicin and rifamycin 40,41 (ESI-5 †) and further confirmed the release of both antibiotics from the core-shell particles. The kinetics profiles revealed that 43% of the rifamycin is released during the first 30 minutes while the release of 50% of the gentamicin requires a four time longer incubation time.…”
Section: Core-shell Nanoparticles and Their Dual Antibiotic Drug Relementioning
confidence: 98%
“…To clarify this point, mass spectrometry analysis of a particle suspension supernatant allowed us to identify the presence of gentamicin and rifamycin 40,41 (ESI-5 †) and further confirmed the release of both antibiotics from the core-shell particles. The kinetics profiles revealed that 43% of the rifamycin is released during the first 30 minutes while the release of 50% of the gentamicin requires a four time longer incubation time.…”
Section: Core-shell Nanoparticles and Their Dual Antibiotic Drug Relementioning
confidence: 98%
“…Pyrimidines represent one of the most active classes of compounds, possessing a wide spectrum of biological activities such as significant in vitro activity against unrelated DNA and RNA viruses including polio herpes viruses, and diuretic, antitumor, anti-HIV, and cardiovascular (Kappe, 1993) activity. In addition to this, various analogs of pyrimidines have been found to possess antibacterial (Sharma et al, 2004;Prakash et al, 2004;Botta et al, 1992;Cieplik et al, 2015), antifungal (Agarwal et al, 2000;Oliver et al, 2016), antileishmanial (Ram et al, 1992;Alptuzun et al, 2013), anti-inflammatory (Amir et al, 2007;Sondhi et al, 2008), analgesic (Vega et al, 1990; Gupta et al, 2011), anti- hypertensive (Hannah & Stevens, 2003;Rana et al, 2004;Alam et al, 2010), antipyretic (Smith & Kan, 1964;El-Sharkawy et al, 2018), antiviral (Balzarini & McGuigan, 2002;Nasr & Gineinah, 2002), antidiabetic (Lee et al, 2005;Reddy et al, 2019), antiallergic (Juby et al, 1979;Gupta et al, 1995), anticonvulsant (Gupta et al, 1994;Shaquiquzzaman et al, 2012), antioxidant (Krivonogov, et al, 2001;Abu-Hashem et al, 2010, antihistaminic (Prasad & Rahaman, 2008;Rahaman et al, 2009), herbicidal (Nezu et al, 1996;Li et al, 2018), and anticancer activities (Abu-Hashem et al, 2010Xie et al, 2009;Kaldrikyan et al, 2000;Mohamed et al, 2...…”
Section: Chemical Contextmentioning
confidence: 99%
“…Changes in the imidazole structures have offered high biological activities that have proven useful for the development of new medicinal agents having improved potency and lesser toxicity. The present review highlights the various synthesized benzimidazoles and their derivatives possessing various activities such as analgesic, anti-inflammatory, anthelmintic, anticancer, anthelmintic, antioxidant, antitubercular, antiviral, antianxiety, acetylcholinesterase inhibitory, and diuretic activity [3].…”
Section: Introductionmentioning
confidence: 99%